Plasticity of snowy plover incubation behaviors in response to risks of nest predation. (26th July 2022) - Ellis, Kristen S; Larsen, Randy T; Ghalambor, Cameron K; Koons, David N
Abstract: Nest predation influences population dynamics and is thought to exert strong selection on the evolution of avian life history. Because parental behaviors can attract the attention of nest predators, incubating birds are predicted to decrease conspicuous behaviors at the nest-site and increase incubation constancy when risks of nest predation are high. We examined whether snowy plovers Charadrius nivosus responded to predator-specific risks of nest predation, using the number of off bouts and daily nest attendance (proportion of time spent incubating) as responses. We quantified risks using predator-specific hazard rates of nest mortality, which varied daily and were based on habitat characteristics at each nest. We assessed the influence of predator-specific risks of nest mortality on incubation behaviors using an individual-centering approach, allowing us to explain variation in incubation behaviors within- and among-breeding pairs. We found increased number of off bouts and nest attendance within-breeding pairs in response to increasing risks of nest predation by foxes ( Vulpes spp.) and gulls ( Larus spp.), but not coyotes ( Canis latrans ) and common ravens ( Corvus corax ). Among breeding pairs across habitats, we found increased nest attendance in response to higher risks of nest predation by foxes, but not coyotes, gulls, or ravens. Breeding pairs differed in the amount of behavioral plasticity they exhibited in response to risks of nest predation. Our results suggest that risks of nest predation differentially influence behavioral responses of snowy plovers depending on the predator species, and the amount of behavioral plasticity may depend on the characteristics of breeding adults. Abstract : Hide How do nesting birds balance trade-offs between the needs of their offspring and themselves, particularly when predators exert varying risks? We show that snowy plovers, a shorebird species where both sexes incubate their nest, vary their incubation behaviors with risks of nest predation by some, but not all nest predator species. Individual breeding pairs were variable in their incubation behaviors and risks of nest predation differentially influence behavioral responses of snowy plovers depending on the predator species.